Evaluating Accounting Information System Controls over Sales Documentation: Evidence from Indonesia's Freight Forwarding Industry - Sya'bania, Anisa Fitri; Rahmadi, Muhammad Arif (Jurnal Ragam Pengabdian, 2026)
The freight forwarding industry relies heavily on complete and accurate sales documentation to support revenue recognition, accounts receivable recording, tax compliance, and reliable financial reporting. The quality of accounting information generated by an Accounting Information System (AIS) depends largely on the effectiveness of internal controls governing sales documentation. However, deficiencies in supporting document completeness, document verification, and interdepartmental coordination continue to undermine accounting information reliability in many freight forwarding companies. This study evaluates the effectiveness of internal controls over sales documentation using the COSO Internal Control Framework within an Indonesian freight forwarding company. A qualitative descriptive approach was employed through observations, document analysis, interviews, and internal control evaluation at PT X. The findings indicate that weaknesses in supporting document completeness, authorization procedures, information and communication, ERP utilization, and monitoring reduce the reliability of accounting records, increase the risk of inaccurate revenue recognition and accounts receivable reporting, and ultimately impair financial reporting quality. The study extends the application of the COSO Internal Control Framework by demonstrating how deficiencies in sales documentation controls influence accounting information quality, thereby providing an Accounting Information Systems perspective that links internal controls with financial reporting reliability. The findings further suggest that strengthening document verification procedures, optimizing ERP integration, and enhancing continuous monitoring can improve accounting information quality and support more reliable financial reporting.